The Role of Traditional Salt Production in Achieving Halal Standards of the Ulamaconsultative Council: Implications for Sustainable Development Goals - Andri Nirwana; Fahmi Arfan; Muthoifin; Zainora Daud; Saifuddin Amin; Syamsul Hidayat; Fahmi Dolles Marshal (Journal of Lifestyle and SDGs Review, 2024)
Indexed by Scopus